Magnetic equivalent circuit model for a two degree-of-freedom rotary-linear machine with transverse flux structure - He, Yaojie (2025)
This paper proposes a magnetic equivalent circuit (MEC) model for a two degree-of-freedom rotary-linear machine with transverse flux structure. The permeance grid is formed according to the flux pattern generated in finite-element method (FEM). By tuning the leakage flux permeance, the electromagnetic performance of the rotary-linear machine calculated by the MEC model shows good alignment to that by FEM. To fully demonstrate the benefits of the MEC model, the calculation accuracy and time consumption comparisons among the MEC model, magnetomotive force (MMF) model, and FEM are conducted. In addition, the MEC model is applied to the parametric study, which proves that the MEC model is capable of obtaining the accurate results under various geometry designs. Based on that, a hierarchical optimization flow is put forward which is a practical method for global optimization on 3D structure. Finally, an experimental prototype is manufactured to verify the proposed concepts.